Diagnosis and Stratification of Pseudomonas aeruginosa Infected Patients by Immunochemical Quantitative Determination of Pyocyanin From Clinical Bacterial Isolates - Rodriguez-Urretavizcaya, Barbara; Pascual, Nuria; Pastells, Carme; Martin-Gomez, Maria Teresa; Vilaplana, Lluïsa; Marco, Maria-Pilar (Frontiers in Cellular and Infection Microbiology, 2021)
The development of a highly sensitive, specific and reliable immunochemical assay to detect pyocyanin (PYO), one of the most important virulence factors (VF) of P. aeruginosa, is here reported. The assay uses a high affinity monoclonal antibody (mAb C.9.1.9.1.1.2.2.) raised against 1-hydroxyphenazine (1-OHphz) hapten derivatives (PC1 a 1:1 mixture of 9-hydroxy- and 6-hydroxy-phenazine-2-carobxylic acids). A selective screening using PYO and1-OHphz on several cloning cycles allowed to choose a clone able to detect PYO at low concentration levels. The microplate-based ELISA developed is able to achieve a LoD of 0.07 nM which is much below the concentrations reported to be found in clinical samples (130 M in sputa and 2.8 M in ear secretions[1]). The ELISA has allowed to investigate the kinetics of release of PYO and 1-OHphz (the main metabolite of PYO) of clinical isolates obtained from P. aeruginosa infected patients and cultured in Mueller-Hinton media. Significant differences have been found between clinical isolates obtained from patients with an acute or a chronic infection ( 6000 nM vs 8 nM of PYO content, respectively corroborated by the analysis of PYO/1-OHphz levels released by 37 clinical isolates obtained from infected patients at different stages. In all cases the levels of 1-OHphz were much lower than those of PYO (at the highest levels 6000 nM vs 300 nM for PYO vs 1-OHphz). The results found point to a real potential of PYO as biomarker of P. aeruginosa infection and the possibility to use such VF also as biomarker for patient stratification[2] and for an effective management of these kind of infections.